Effectiveness of health education in the self-care and adherence of patients with heart failure: a meta-analysis - Juliana de Melo Vellozo Pereira Tinoco; Lyvia da Silva Figueiredo; Paula Vanessa Peclat Flores; Bruna Lins Rocha de Padua; Evandro Tinoco Mesquita; Ana Carla Dantas Cavalcanti (Universidade de São Paulo, 2021)
Objective: to evaluate in the literature the effectiveness of the health education interventions in self-care and adherence to treatment of patients with Chronic Heart Failure. Method: a systematic review with meta-analysis. Studies were selected that compared health education interventions with the usual care to assess the outcomes of adherence and self-care. The quality of the methodological evidence was assessed by the Grading of Recommendations, Assessment, Development and Evaluation system. Results: the educational interventions were more effective in relation to the usual care in the outcome of adherence (fixed effect=0-3841; p-value <0.001). There was no statistical difference in the outcome of self-care (fixed effect=0.0063; p-value=0.898). Conclusion: the educational interventions improved the outcome of adherence, though not self-care in the patient with Heart Failure.